Gambaran Subjective Well-Being pada Perempuan yang Mengalami Involuntary Childlessness dalam Keluarga Batak - Saneth Aurelia Yosephine; Dhevy Setya Wibawa (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
Women naturally supposed to be able to conceive and give birth to children. This perception puts pressure on women who experience involuntary childlessness. Cultural factors are one of the factors that plays a role in shaping subjective well-being in women who experience involuntary childlessness from the Batak tribe. The pressure that is felt not only comes from herself, but also from her family, because of the strength of the Hagabeon value. The amount of pressure felt by the woman also had an impact on the evaluation of her life. This qualitative study uses a semi-structured interview technique to see the description of the subjective well-being of women who experience involuntary childlessness in a Batak family based on Diener's Subjective Well-Being theory. The results show that women with involuntary childlessness has a tendency to have less fine subjective well-being. The pressure due to the appreciation of the Hagabeon values, or the support provided by the family, is a factor that plays a role in the differences in the subjective well-being among the participants. In addition, physical and occupational health factors also play a role in the formation of a subjective well-being.